Synergistic Flame Retardancy of Aluminium Dipropyl-Phosphinate and Melamine Cyanurate in Polyamide-6 - He, Wei; Yuan, Zhigang; Liu, Yujia; Wang, Yuchong; Tang*, Linsheng (Asian Journal of Chemistry, 2014)
The synergistic flame retardancy of aluminium dipropylphosphinate (ADPP) and melamine cyanurate (MCA) in polyamide 6 (PA6) was studied by the limiting oxygen index (LOI) measurement, the vertical burning test, the cone calorimeter test and the mechanism was also discussed by residural analysis. It was found that there was no obvious synergistic flame retardancy between aluminium dipropylphosphinate and melamine cyanurate in polyamide 6. Compared with the flame-retarded polyamide 6 (FR-PA6) with aluminium dipropylphosphinate, the limiting oxygen index of the FR-PA6 with aluminium dipropylphosphinate/melamine cyanurate with appropriate weight ratios increased slightly, but vertical burning class, heat release rate (HRR), peak heat release rate (PHRR), mass loss rate (MLR) and total heat release (THR) were similar. Additionally, aluminium dipropylphosphinate/melamine cyanurate had a greater influence on the thermal stability of the composites than aluminium dipropylphosphinate and melamine cyanurate. The analysis of the residues obtained in cone calorimeter test showed that aluminium dipropylphosphinate played the role of flame retardancy by gaseous and condensed phase mechanisms. On one hand, aluminium dipropylphosphinate were decomposed into non-volatile aluminum phosphate and promoted the carbonization of polyamide 6 and the formed intumescent layer resulted in flame retardancy by the barrier effect on heat, air and decomposition products, on the other hand, it was decomposed into volatile phosphorus compounds which brought about flame retardancy by flame inhibition.